POSSIBILITIES OF THE “CONFUSED LOGICAL CHAIN” METHOD IN ASSESSING STUDENTS’ KNOWLEDGE (Global Conference on Medical and Health Sciences, 2026)
This article discusses the use of the “confused logical chain” method for assessing students’ level of knowledge during practical classes in the Dynamics section of the course Theoretical Mechanics. The study examines the effectiveness of this method in evaluating students’ understanding of theoretical concepts, logical thinking abilities, and problem-solving skills in practical lessons.
Keywords: theoretical mechanics, dynamics, force, mass, law of motion, equation, differential equation, initial conditions, integration constants, first problem, second fundamental problem.